Pyroelectric nanoplates for reduction of CO2 to methanol driven by temperature-variation - Lingbo Xiao (Nature Portfolio, 2021)
CO2 is a problematic greenhouse gas, although its conversion to alternative fuels represents a promising approach to limit its long-term effects. Here, the authors demonstrate that CO2 can be reduced to methanol through pyroelectric catalysis under temperature variation near room temperature.